The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1088/0957-0233/9/4/018
|View full text |Cite
|
Sign up to set email alerts
|

Errors and uncertainties in the ultrasonic pulse-echo reflectometry method for measuring acoustic impedance

Abstract: Ultrasonic pulse-echo reflectometry provides a convenient method to measure the acoustic impedance of a layer of unknown material bonded to a substrate of another material whose acoustic properties are known. The amplitudes of echoes from the interface are used to calculate the interface reflection coefficient and, from this and a knowledge of the properties of the substrate material, the unknown impedance is obtained. The technique has potential for assessment of adhesive cure and measurement of mechanical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In eq 2 Z q is the acoustic impedance of the quartz (i.e., Z q = (μ q ρ q ) 1/2 ), where μ q is the shear modulus of quartz in the plane of the quartz disc used as the oscillator and ρ q is the density of quartz. Quartz has a density of 2.66 g/cm 3 . The shear modulus for the AT cut quartz used in our experiments is 2.95 × 10 10 Pa, giving Z q = 8.84 × 10 6 kg/m 2 s. The complex impedance is defined as the ratio of the interfacial shear stress, σ n *, to the velocity of the shear wave, uṅ *:…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eq 2 Z q is the acoustic impedance of the quartz (i.e., Z q = (μ q ρ q ) 1/2 ), where μ q is the shear modulus of quartz in the plane of the quartz disc used as the oscillator and ρ q is the density of quartz. Quartz has a density of 2.66 g/cm 3 . The shear modulus for the AT cut quartz used in our experiments is 2.95 × 10 10 Pa, giving Z q = 8.84 × 10 6 kg/m 2 s. The complex impedance is defined as the ratio of the interfacial shear stress, σ n *, to the velocity of the shear wave, uṅ *:…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 Equation 10 can be used to determine some general guidelines for the use of quartz crystal resonators as sensors immersed in bulk fluids. For an AT cut quartz crystal operating at a fundamental resonance frequency of 5 MHz exposed on one side to water (η = 10 −3 Pa s and ρ = 1 g/cm 3 ), ΔΓ = −Δf = 713 Hz. As a general rule, we have found that high-quality data can be obtained when Γ is less than ∼20 kHz, corresponding to solution viscosities of less than about 0.5 Pa s (for ρ = 1 g/ cm 3 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, it has been shown that the measurements done via the reflection method are less accurate than those done with a transmission configuration [12]. In order to improve the accuracy of the measurements done by reflectometry, one can work with multiple reflections instead of simple one, as it was done by Longin et al [13] on polydimethylsiloxane polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The values and errors obtained for the reflection coefficient, phase shift and loss modulus as a function of the delay line material are reported in Table 2 [25]. One can notice that according to theory and to viscosity measurements, G 00 should be equal to 81.7 MPa because G 00 = xg.…”
Section: Resultsmentioning
confidence: 97%